Do we need to count everything? Monitoring conspicuous epibenthic communities using seabed imagery. (February 2019) - Barry, Jon; Murray, Joanna; Ware, Suzanne
Highlights: The Generalised Visual Fast Count (GVFC) method reduces the number of animals counted by 90%. GVFC gives good estimates of abundance for five key species. GVFC performs better than other sub-sampling methods such as random selection of segments within video tows. Abstract: The purpose of this paper is to identify whether sub-sampling methods such as the Generalised Visual Fast Count can provide adequate inferences from video data. This is done by comparing the results from sub-sampling video data on species counts from the Fladen Grounds, U.K. with those results from the full data set. We show that the GVFC method can provide complete information on species richness and that estimates of key species' densities are adequate compared to those from the full data. This is achieved from counting only 10% of the individuals present – thus saving time and money.